Age effects in second language learning: stepping stones toward better understanding (2013)
"As should be apparent by now, the position taken in this book is that second language teaching should focus on encouraging acquisition, on providing input that stimulates the subconscious language acquisition potential all normal human beings have. This does not mean to say, however, that there is no room at all for conscious learning. Conscious learning does have a role, but it is no longer the lead actor in the play." (Krashen and Terrell, 1981). In his article, the author DeKeyser (2013), points out the relevance attained to the Second Language Learning, with controversial issues such as conceptual misunderstanding and methodological difficulties. On the other hand, the author seeks that the debate between each other is be able to agree on them, through the suggestions for improvement in subject selection, data collection, and instrumentation to understand how crucial is the age effects for educational policy and curriculum design; and how different are the foreign language learning from second language learning environments.